Financial Ratio Analysis To Assess Financial Performance With Bank (Case Study At Bank Btpn Listed On The Indonesia Stock Exchange, 2018-2020) - Indah Melisa Putri; Yanna Eka Pratiwi; Siwidyah Desi Lastianti (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
A bank can be said to be successful if the bank is able and can be measured based on the financial performance of the bank. By looking at the financial performance, it can be concluded that the banking condition is in good condition or not. This study aims to analyze the financial performance of banks listed on the Indonesian Stock Exchange in the 2018-2020 period based on the liquidity ratio with the current ratio and quick ratio, then the solvency ratio with the debt ratio to assets and debt ratio to equity and the last is the profitability ratio with ROA, ROE, and profit margin ratio. This study uses data analysis techniques, quantitative descriptive approach and data collection techniques used in this study are documentation and the data studied are in the form of annual financial reports. The population used in this study is Bank BTPN which is listed on the Indonesia Stock Exchange for the period 2018-2020. The sampling technique in this research is purposive sampling. The results of this study are 4. In general, judging from the four financial ratios, it can be said that the financial performance of banks has decreased in the last year.